The spectrum of liver diseases in HIV infected individuals at an HIV treatment clinic in Kampala, Uganda - Ocama, Ponsiano (Makerere Medical School, 2008)
BACKGROUND: Liver diseases are common in patients with HIV due to viral hepatitis B and C co-infections, opportunistic infections or malignancies, antiretroviral drugs and drugs for opportunistic infections. OBJECTIVE: To describe the spectrum of liver diseases in HIV-infected patients attending an HIV clinic in Kampala, Uganda. METHOD: Consecutive patients presenting with jaundice, right upper quadrant pain with fever or malaise, ascites and/or tender hepatomegaly were recruited and underwent investigations to evaluate the cause of their liver disease. RESULTS: Seventy-seven consecutive patients were recruited over an eleven month period. Of these, 23 (30%) had increased transaminases because of nevirapine (NVP) and/or isoniazid (INH) hepatotoxicity. Although 14 (61%) patients with drug-induced liver disease presented with jaundice, all recovered with drug discontinuation. Hepatitis B surface antigen was positive in 11 (15%) patients while anti-hepatitis C antibody was reactive in only 2 (3%). Probable granulomatous hepatitis due to tuberculosis was diagnosed in 7 (9%) patients and all responded to anti-TB therapy. Other diagnoses included alcoholic liver disease, AIDS cholangiopathy, hepatocellular carcinoma, schistosomiasis, haemangioma and hepatic adenoma. Twelve (16%) patients died during follow-up of which 7 (9%) died because of liver disease. CONCLUSION: Drug history, liver enzyme studies, ultrasound, and hepatitis B and C investigations identified the probable etiology in 60 (78%) of 77 patients with HIV infection presenting with symptoms and/or signs of liver disease.